Good Corporate Governance from an Accounting Theory Perspective: A Literature Review - Laras Angelia Nirwana Sari (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to provide a comprehensive theoretical mapping of how Good Corporate Governance (GCG) is understood and examined through various accounting theories. While prior studies often emphasize empirical and regulatory compliance aspects, this literature review focuses on conceptual and theoretical foundations. Drawing from five dominant accounting theories Agency Theory, Positive Accounting Theory, Normative Accounting Theory, Critical Accounting Theory, and Social Accounting Theory. This article analyzes how each perspective contributes to the development of GCG. The findings show that most studies still rely heavily on Agency Theory, reflecting an economic-instrumental view of governance. In contrast, normative, critical, and social approaches remain underutilized, especially in the Indonesian context. The article suggests that expanding theoretical lenses is crucial to address the ethical, social, and sustainability dimensions of corporate governance. This study contributes to the academic discourse by synthesizing theoretical frameworks and encouraging a values-based approach to GCG.